Correction: Yang et al. Opening and Closure of the Sulu Sea: Revealed by Its Peripheral Subduction and Collision Processes. J. Mar. Sci. Eng. 2024, 12, 1456 - Yunliu Yang; Xinong Xie; Yunlong He; Hao Chen (Journal of Marine Science and Engineering, 2025)
In the original publication [...]